Which way forward? people,forests, and policymaking in indonesia - Colfer, Carol J. Pierce; Resusudarmo, Ida Aju Pradnja (Resources for the Future ; Center for International Forestry Research ; Institute of Southeast Asian Studies, 2002)
Indonesia contains some of Asia's most biodiverse and threatened forests. The challenges result from both long-term management problems and the political, social, and economic turmoil. This book focuses on what can be done differently to counter the destruction of forests due to asset-stripping, corruption, and the absence of government authority